The continental record of Marine Isotope Stage 11 (Middle Pleistocene) on the Iberian Peninsula characterized by herpetofaunal assemblages. (11th August 2015) - Blain, Hugues‐Alexandre; Lozano‐Fernández, Iván; Ollé, Andreu; Rodríguez, Jesus; Santonja, Manuel; Pérez‐González, Alfredo
ABSTRACT: Marine Isotope Stage (MIS) 11 in Iberia is documented at three main Acheulean archaeological sites: Gran Dolina (Burgos, Atapuerca), Áridos‐1 (Madrid) and Ambrona (Soria). As the amphibians and reptiles recovered as fossils from these sites are not extinct and their ecology can be directly studied, mutual climatic range and habitat weighting methods have been applied to the herpetofaunal assemblages to estimate climatic and environmental parameters during MIS 11. Compared with today, mean annual temperature varies from +2.7 to +0.3 °C and mean annual precipitation varies from +311.7 to +74.4 mm, suggesting, in accordance with the numerical dates for each locality, a progressive decrease in temperature and rainfall from the fully interglacial conditions of MIS 11c to the end of MIS 11. The presence of woodland areas is also well substantiated throughout the duration of MIS 11, at least during the interglacial and interstadial periods.